Influence of Respiratory Exercises on the Functional State of the Cardiovascular System Under Different Physical Activities of Students - Serman, Taras (Journal of Vasyl Stefanyk Precarpathian National University, 2022)
The article stresses that the state of the cardiovascular system determines the level of physical performance. Maintaining the required level of metabolic processes is necessary for efficient mechanisms of energy supply and dynamic work. The researcher proves that activation of respiratory function contributes to such support. Under the influence of systematic breathing exercises in the body develops a set of structural and functional changes aimed at optimizing the functioning of the whole organism and its individual systems. The study involved 35 lyceum students aged 14 years, who were engaged in the developed system for 1.5 years. Each lesson consisted of six parts. In the first, third and fifth parts, they performed exercises with dynamic, and in the second and fourth – with static load. In the first three parts they were combined with breathing exercises with increasing duration of individual phases of breathing, in 4-6 parts – only with deepening of exhalation. The sixth part (relaxation) was performed in a horizontal position. The purpose of the work is to determine the impact of breathing exercises during each part of the lesson on the activity of the cardiovascular system. It has been established that certain features of fatigue and recovery during different types of muscular work in a specific sequence are a reliable physiological basis for improving the health and training effect of physical training in combination with breathing exercises. The results of the experiment on the implementation of our system of health-improving training sessions of respiratory gymnastics prove that changes in work power, nature of muscle contractions and body position during training create conditions for improving adaptive compensatory reactions to different types of loads.